Vulnerabilidades de mulheres com filhos diagnosticados com sífilis congênita - Mesquita, Anna Larissa Moraes (2021)
The syphilis is among the sexually transmitted infections that are undergoing a feminization process, a fact that becomes more worrying because it includes pregnant women, and when left untreated it can result in its vertical transmission, a condition with the greatest impact on public health. The transmission can occur due to vulnerabilities, and the lack of affective family support can cause situations of precariousness of the subject resulting in health vulnerability. The objective was to describe the elements of health vulnerability of women with children with congenital syphilis. The method used was a multiple case study conducted with nine women who had children diagnosed with congenital syphilis in 2017, residents of the municipality of Sobral / CE. Data collection took place from August to December 2019, through notification forms and semi-structured interviews. For data analysis, the development of case description and treatment from scratch as general strategies and the cross-synthesis of cases as an analytical technique, based on the theoretical framework of Health Vulnerability, were also used Qualitative Data Analysis software for organizing data The research was approved by the Research Ethics Committee under opinion number 3,137,516. From the immersion and analysis of the interviews, 180 references were identified, which were classified into six categories grouped according to the elements of health vulnerability. Related to the subject: Functional literacy of women regarding syphilis, Psycho-emotional situation of women facing syphilis, Interpersonal relationships of women and Behaviors of women and their partners. And in relation to the social element were: Women's social networks and supports during pregnancy and the puerperium and Programmatic Situation of health services that assist women who had children diagnosed with congenital syphilis. Thus, the study of multiple cases allowed immersion in the singularities of women, individually and collectively, seeking to highlight congruences and dichotomies among the vulnerabilities experienced by them in their different contexts. The study contributes to society with the dissemination of the concept of vulnerability in health, with the expansion of the vision of health and contexts in which the subject is inserted.